2017
DOI: 10.4315/0362-028x.jfp-17-210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Surface Sampling Methods for Microbiological and Chemical Analyses To Assess the Presence of Biofilms in Food Companies

Abstract: Biofilms are an important source of contamination in food companies, yet the composition of biofilms in practice is still mostly unknown. The chemical and microbiological characterization of surface samples taken after cleaning and disinfection is very important to distinguish free-living bacteria from the attached bacteria in biofilms. In this study, sampling methods that are potentially useful for both chemical and microbiological analyses of surface samples were evaluated. In the manufacturing facilities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In this study, 63% of the samples where chemical analysis was performed contained at least one of the chemical components (proteins, carbohydrates or uronic acids). The presence of high numbers of microorganisms in combination with chemical components (possibly originating from EPS or organic pollution) sampled after the application of disinfectants on the surface can be an indication for the presence of a biofilm [33]. This means that in this study, 63% of the analysed surfaces would be identified as carrying biofilm.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In this study, 63% of the samples where chemical analysis was performed contained at least one of the chemical components (proteins, carbohydrates or uronic acids). The presence of high numbers of microorganisms in combination with chemical components (possibly originating from EPS or organic pollution) sampled after the application of disinfectants on the surface can be an indication for the presence of a biofilm [33]. This means that in this study, 63% of the analysed surfaces would be identified as carrying biofilm.…”
Section: Discussionmentioning
confidence: 92%
“…This means that in this study, 63% of the analysed surfaces would be identified as carrying biofilm. This is a much higher number compared to surfaces in the food industry where the presence of biofilm (determined in the same way as in the current study) was suspected in 17% of the cases [33].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a previous study (24), residual contamination on food contact surfaces after C&D was mapped and characterized in terms of bacterial levels and chemical composition. Bacterial contamination after C&D of food contact surfaces ranged from ,0.22 to 7.23 log CFU/100 cm 2 (mean 6 standard deviation of 3.62 6 1.20 log CFU/ 100 cm 2 ) on contaminated surfaces.…”
mentioning
confidence: 99%